Fracasos endodónticos causados por la deficiente obturación de conductos radiculares en primeros molares permanentes. - Escobar Punina, Guadalupe de los Ángeles (2024)
This project addresses the problem of endodontic failures in first permanent molars, a branch of dentistry focused on diagnosing and treating diseases of the dental pulp and periapical tissues. Approximately 10% of endodontic treatments fail, the leading causes being bacterial infection and technical and anatomical factors. A study in the USA in 2019 highlighted the correlation between bacterial infections in root canals and periapical granulomas in endodontic failures. The researcher applied a bibliographic review using databases such as ProQuest, PubMed, and Google Scholar, selection criteria, and the PRISMA methodology. The approach was qualitative and descriptive. The results reveal the importance of complete disinfection of the ducts, precision in instrumentation and obturation, proper choice of irrigants and medications, and consideration of factors such as the length of obturation and root anatomy. It also highlights the bacterial resistance, especially of microorganisms such as Enterococcus faecalis. Therefore, it was possible to identify that success in endodontics requires a comprehensive approach that addresses microbiological, technical, and material selection aspects. Continuing education and adopting advanced technologies to overcome challenges of bacterial resistance and iatrogenic errors are emphasized. It is recommended to improve the training of professionals in advanced obturation techniques, perform detailed anatomical assessments, adopt a comprehensive approach to treatment planning, use effective disinfection strategies, and conduct accurate post-treatment follow-up. These measures can potentially reduce the incidence of endodontic failures in first permanent molars and improve dental care.